Family Support Group to Reduce Loneliness in Caregiver of Mental Health Disorders Patients - Zulfian Kurniadi Muftikhar; Asroful Hulam Zamroni (Jurnal Psikiatri Surabaya, 2024)
Introduction: Caring for patients with mental health disorders causes loneliness in caregivers. Therefore, interventions are needed to reduce the level of loneliness in caregivers of patients with mental health disorders. This literature review study aims to determine the effectiveness of family support groups in reducing loneliness in caregivers of patients with mental health disorders. Methods: This study used the ScienceDirect and Google Scholar databases and were searched using the following keywords family support group AND reduce AND loneliness AND caregiver And Mental Health Disorder in filtered journals published in 2013-2023. Results: Caregivers of mental health patients experience the main psychosocial problem, namely loneliness in the process of caring for patients with mental health disorders. Loneliness in caregivers of patients with mental health disorders is caused by stigma which causes feelings of isolation, disconnection, and lack of social relationships, increased stress, and emotional tension. Family support groups can reduce the level of loneliness in caregivers of patients with mental health disorders. Conclusion: Family group support intervention creates effective coping so that the cognitive control network in processing socio-affective information becomes a reflection. This stimulates the reduction of thoughts and perceptions which have an impact on reducing feelings of loneliness. Keywords: Caregiver, Family Support Group, Loneliness, Mental Health Disorder, Reduce